2013
DOI: 10.1111/hepr.12151
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression analysis of Golgi apparatus proteomes in hepatocellular carcinomas and the surrounding liver tissues

Abstract: The differentially expressed proteins may provide new insight into HCC biology and potential diagnostic and therapeutic biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…(2014) focused on the Golgi apparatus proteomes in HCC tissues and adjacent liver tissues; proteins related to the different BPs were found [25]. It is reported that GP73 acts as a key oncogene in HCC by regulating metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…(2014) focused on the Golgi apparatus proteomes in HCC tissues and adjacent liver tissues; proteins related to the different BPs were found [25]. It is reported that GP73 acts as a key oncogene in HCC by regulating metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Using 2D–SDS-PAGE, Yang et al screened for Golgi proteins up- or downregulated in HCC [21]. They did not pick up the UNC50 protein spot in the matrix-assisted laser desorption/ionization–time-of-flight mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a role in deoxidation, glycogen storage, detoxification, and secretory protein synthesis in mammals [1,2]. The liver is also the largest digestive gland in the digestive system and is closely related to digestion and absorption [3]. Liver diseases are usually divided into viral liver disease (viral hepatitis A, B, C, D, and E, etc.)…”
Section: Introductionmentioning
confidence: 99%